THE DEVELOPMENT OF NATURAL DYED FABRIC PRODUCT WITH SHIBORI FABRIC DYEING TECHNIQUE - Nuttida Pujeeb (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research on the development of natural dyed fabric products with Shibori fabric dyeing technique 1) studied concepts and processes of the Thai natural dyed fabric products 2) studied concepts and processes of the Shibori fabric dyeing technique from Japan and 3) developed the Shibori fabric dyeing technique by using the research methodology and development to study in-depth knowledge from resources in which the findings were used to develop new products. The researcher divided the research methodology into 4 phases. It was found that 1) cultural conservation, creation and development along with benefits of the Thai natural dyed fabric products could be divided into 2 models including cold dye and hot dye where each uses different natural products and processes depending on the availability of local resources and the knowledge passed on from generation to generation. The strength of Thai natural dyed fabric products is a variety of natural materials of colors. The weaknesses are the inability to create definite patterns and the lack of data as well as development to meet the standard. 2) cultural conservation, creation and development as well as benefits of the Shibori fabric dyeing technique, this dye folding from Japan is with the identity that prescribes the patterns on the fabrics by folding and sowing it. This is a well-established technique. 3) the Shibori natural fabric dyeing technique that the researcher invented used natural colors in Thailand combined with the folding technique from Japan resulting beautiful patterns and setting the standard with various bright colors.